Syntheses of thiazole-containing macroheterocycles related to porphycene - Nußbaumer, Thomas; Neidlein, Richard (Helvetica chimica acta, 2000)
The syntheses of 2,2′-bithiazole-containing and related expanded macrocycles 13 - 16 were accomplished by the McMurry coupling reaction of the corresponding [2,2′-bithiazole]-5,5′-dicarbaldehyde 6c and 2,2′-(1,4-phenylene)bis[thiazole-5-carbaldehyde] 7, readily available by a two-step reaction sequence. The success of the dimerization strongly depends on the steric repulsion of the substituents vicinal to the CHO group.
Gesehen am 28.04.2017